Thermodynamical Quantities of Chalcogenide Dimers (O2, S2, Se2, and Te2) from Spectroscopic Data - Shipra Tiwari; Pavitra Tandon; K. N. Uttam (Journal of Spectroscopy)
Attempts have been made to calculate the thermodynamical quantities of diatomic molecules such as O2, S2, Se2, and Te2 from spectroscopic data with the help of partition function theory. The results have been calculated in the temperature range 100–3000°C. In order to increase accuracy of the calculated quantities, we have incorporated nonrigidity, anharmonicity, and stretching effects of molecules. The variation of these quantities with temperature have been studied and explained in terms of various modes of molecular motions.